Dual inhibition of CB1 receptors and iNOS, as a potential novel approach to the pharmacological management of acute and long COVID‐19. (17th April 2021) - Cinar, Resat; Iyer, Malliga R.; Kunos, George
Abstract : COVID‐19 (SARS‐CoV‐2) causes multiple inflammatory complications, resulting not only in severe lung inflammation but also harm to other organs. Although the current focus is on the management of acute COVID‐19, there is growing concern about long‐term effects of COVID‐19 (Long Covid), such as fibroproliferative changes in the lung, heart and kidney. Therefore, the identification of therapeutic targets not only for the management of acute COVID‐19 but also for preventing Long Covid are needed, and would mitigate against long‐lasting health burden and economic costs, in addition to saving lives. COVID‐19 induces pathological changes via multiple pathways, which could be targeted simultaneously for optimal effect. We discuss the potential pathologic function of increased activity of the endocannabinoid/CB1 receptor system and inducible NO synthase (iNOS). We advocate a polypharmacology approach, wherein a single chemical entity simultaneously interacts with CB1 receptors and iNOS causing inhibition, as a potential therapeutic strategy for COVID‐19‐related health complications. LINKED ARTICLES: This article is part of a themed issue on The second wave: are we any closer to efficacious pharmacotherapy for COVID 19? (BJP 75th Anniversary). To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.10/issuetoc